Understanding the bullying phenomenon through the eyes of the youth football coaches in the Portuguese region of Tâmega e Sousa - Vaz, Cátia; Teixeira, José Eduardo; Portella, Daniel L.; Monteiro, Diogo; Forte, Pedro; Silva-Santos, Sandra; Ribeiro, Joana (Frontiers in Sports and Active Living, 2025)
IntroductionBullying is a serious social problem affecting, primarily, children and adolescents in educational and sports environments. Analyzing this phenomenon in contexts where children meet and interact, like football schools/clubs, is critical. The study aims to investigate how youth football coaches perceive bullying and their role in addressing it, as well as to explore bullying as a social phenomenon through the lens of coaches' knowledge and experiences.MethodsTwenty-four coaches from the Portuguese region of Tâmega and Sousa highlighted their awareness and concern about the growth of bullying in football, and that everyone is involved (70.8%).ResultsThe victims are “younger” (83.3%) and “teammates” (54.2%) of the aggressors. Assaults occur mostly due to the victims' “physical characteristics”, “behaviors/attitudes” and “sexual orientation”. Coaches believe that the aggressors are “opposing team fans” (25.5%), “teammates” (22.6%), “male” (66.67%), “older” than the victims (75%), and attack in “locker rooms” (23.81%) and in “stands” (17.46%). They consider that bullying victims do not seek help (91.67%) due to “fear” (79.17%), and that the sports agents react indifferently (50%) to acts of this nature.ConclusionsCoaches acknowledge that they can play a decisive role in preventing this issue, but do not feel fully prepared to identify warning signs and act in accordance, emphasizing the need to improve coach education through new prevention strategies.